Basal ganglia damage and impaired visual function in the newborn infant. Issue 2 (1st September 1997) - Mercuri, Eugenio; Atkinson, Janette; Braddick, Oliver; Anker, Shirley; Cowan, Frances; Rutherford, Mary; Pennock, Jackie; Dubowitz, Lilly
Abstract : AIM: To examine the effects of early lesions in the visual pathway on visual function; and to identify early prognostic indicators of visual abnormalities. METHODS: The visual function of 37 infants with perinatal brain lesions on magnetic resonance imaging was assessed using behavioural and electrophysiological variables. RESULTS: Normal visual behaviour was observed in most infants with large bilateral occipital lesions, but all the infants with associated basal ganglia involvement had abnormal visual function. Visual abnormalities were also present in six infants with isolated basal ganglia lesions. CONCLUSIONS: These observations suggest that basal ganglia may have an integral role in human visual development and that their presence on neonatal MRI could be an early marker of abnormal visual function.